Influence of Dorper lamb development from birth to 120 days of age on clinical and echocardiographic parameters - Aleixo, Amanda Sarita Cruz [UNESP]; Ferreira, Danilo Otávio Laurenti; Tsunemi, Miriam Harumi [UNESP]; Chiacchio, Simone Biagio [UNESP]; Lourenço, Maria Lucia Gomes [UNESP] (Springer Nature, 2022)
The expansion of the sheep model in research represents an attractive and economically beneficial academic reason for investigations in sheep echocardiography. The present study aimed to evaluate the clinical and echocardiographic parameters in Dorper lambs during the developmental period. Emphasis was placed on the use of the species in translational research for the echocardiographic diagnosis of congenital heart diseases, which can contribute to improvements in interventionist techniques. Ten Dorper lambs were evaluated at the following time points: 24 h after birth and 7, 14, 21, 30, 60, 90 and 120 days of age. Clinical parameters were compiled, and echocardiogram records were obtained without sedation. Rectal temperature was lower on the first day compared to the others. From 21 days of life, there was a reduction in HR, with differences between time points. Mean and systolic blood pressure differed, with the highest values at 90 and 120 days of age. The thickness of the interventricular septum in diastole (IVSd) increased as age progressed, with the highest value at 120 days of age, and the same occurred for LVIDd (left ventricle internal diameter in diastole), LVFWd (left ventricular free wall thickness in diastole), IVSs (interventricular septum thickness in systole), LVIDs (left ventricle internal diameter in systole) and LVFWs (left ventricular free wall thickness in systole). There were differences in the size of the LA, Ao and LA/Ao ratio, which were greater at 90 days and 120 days of age. Echocardiographic changes accompany the development of lambs, where changes in echocardiographic parameters are evident with advancing age. The echocardiographic measurements in lambs obtained in the present study are similar to those in newborns.